Effects of Moisture-Induced Crystallization on the Aerosol Performance of Spray Dried Amorphous Ciprofloxacin Powder Formulations - Shetty, N.; Zeng, L.; Mangal, S.; Nie, H.; Rowles, Matthew; Guo, R.; Han, Y.; Park, J.; Zhou, Q. (AAPS, 2018)
© 2017, Springer Science+Business Media, LLC, part of Springer Nature. Purpose: This study aims to investigate the influence of different storage humidity conditions on crystallization and aerosol performance of inhalable spray dried amorphous powder formulations (Ciprofloxacin hydrochloride as the model drug). Methods: The spray dried samples were stored at 20%, 55% and 75% relative humidity (RH). Crystallinity was monitored by Powder X-ray diffraction (PXRD), and particle morphology was measured by scanning electron microscopy (SEM) and atomic force microscopy (AFM). Aerosol performance was evaluated using a multi-stage liquid impinger (MSLI). Results: PXRD diffractograms showed the spray dried Ciprofloxacin stored at 20% RH for three weeks were amorphous; whereas those stored at 55% RH and 75% RH started crystallizing after one hour. Fine particle fraction (FPF) of the particles was improved from 28% to 42% after storage at 55% RH for three days. Such improvement was attributed to the crystallization of amorphous powders, which led to increased particle roughness and reduced particulate contact area, as visualized by SEM and quantified by AFM. A linear relationship was observed between degree of crystallinity/crystallite size and FPF (R 2 = 0.94 and R 2 = 0.96, respectively). However, deterioration in aerosol performance was observed after storage at 75% RH due to formation of inter-particulate liquid/solid bridges, as confirmed by SEM. Conclusions: This study provides a fundamental understanding in moisture-induced physical and aerosol instability of the spray dried powder formulations.